THE PERFORMANCE STRUCTURE OF INDIVIDUAL COMPETITION IN BIATHLON (Kinesiology, 2022)
Individual biathlon competition as an event consists of a number of segments (variables), i.e. cross-country skiing time, range time, so-called time difference, and shooting accuracy. In the research part, the study analysed the interrelations of these variables and their correlations with competitive performance at the Biathlon World Championship individual competition. Regression analysis showed that total cross-country skiing time was the most important determinant of competitive performance (55%). Total shooting performance prone and standing explains 39.5%, total range time accounts for 5% of the criterion variable, and time difference for 0.5%. The contestants hit 80.5% of all targets in this competition. Factor analysis determined seven factors that logically completed the competition outcome in a biathlon individual competition. These factors are: cross-country skiing performance; shooting time and range time; time difference; accuracy shooting 1 and total time in lap 1; accuracy shooting 2 and total time in lap 2; accuracy shooting 4 and total time in lap 4; and accuracy shooting 3 and total time in lap 3. Although we found in this competition a somewhat dominant contribution of the cross- country skiing itself to the final competitive performance, shooting accuracy is also very important in an individual biathlon competition. The results of men’s individual biathlon competitions at the last Olympics and World Championships show that it is still possible to win a medal with only one missed shot (two missed shots can only be afforded by the rare biathletes who are extremely fast skiers).Key words: Biathlon, individual competition, competition variables, competitive performance